1990
DOI: 10.2190/rth3-c7wy-17gg-d9kq
|View full text |Cite
|
Sign up to set email alerts
|

Grandparents and Adult Grandchildren: What Do They Do for One Another?

Abstract: This article reports findings from a study in which the functional exchange of services, emotional (expressive) and tangible (instrumental) between grandparents and adult grandchildren were examined. The reciprocal (equivalent) and nonreciprocal (excessive giving or receiving) exchange of services was measured by the frequency of exchange and perception of potential support between the dyad. Noninstitutionalized Jewish grandparents (118, 65+ years of age) with at least one adult grandchild (18+ years of age) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 6 publications
1
23
0
3
Order By: Relevance
“…Grandparents frequently support grandchildren when parents are unable or unwilling to do so (Kemp, 2004; Kornhaber & Woodward, 1985; Langer, 1990; Roberto, Allen & Blieszner, 2001). In her seminal work, Troll (1983) characterizes grandparents as the “family watchdog[s]” who “monitor[s] the state of the family functioning and step[s] in only when they are needed,” (p. 64) often appearing uninvolved.…”
Section: Expectations Of Grandparentsmentioning
confidence: 99%
“…Grandparents frequently support grandchildren when parents are unable or unwilling to do so (Kemp, 2004; Kornhaber & Woodward, 1985; Langer, 1990; Roberto, Allen & Blieszner, 2001). In her seminal work, Troll (1983) characterizes grandparents as the “family watchdog[s]” who “monitor[s] the state of the family functioning and step[s] in only when they are needed,” (p. 64) often appearing uninvolved.…”
Section: Expectations Of Grandparentsmentioning
confidence: 99%
“…An example of this kind of study can be found in Langer (1990), who observed that, when a sample of grandparents assessed their relationship with adult grandchildren, they perceived what they gave to their grandchildren, both as instrumental and expressive support, was more than what their grandchildren gave them.…”
Section: Studying the Relationship From Both Sidesmentioning
confidence: 99%
“…A pesar de ello, el balance de apoyo cambia cuando los nietos llegan a la adultez; los abuelos refieren que reciben más apoyo expresivo e instrumental de sus nietos adultos del que ellos dan. Así lo muestra el trabajo de Langer (1990) y el de Kivett (1985). En el estudio de Kivett (1985) sobre una muestra de abuelos encontró que tres cuartas partes de ellos sentían que sus nietos eran responsables de proveerles de apoyo financiero y ayuda instrumental en los momentos de necesidad.…”
Section: La Relación Entre Abuelos Y Nietos N" 38 Mayo-agosto 2004unclassified